2021
DOI: 10.14429/djlit.42.1.17304
|View full text |Cite
|
Sign up to set email alerts
|

Users Awareness and Usage of Open Educational Resources in Central Universities of North India

Abstract: Technological advancements and open educational resources (OER) together have opened up wider opportunities to access globally created educational resources by anyone across the globe. A paradigm shift has been witnessed in the format of learning resources, their access methods, and the medium of delivery of the knowledge content. The findings of this research reveal that the academic community of central universities (CU) of North India is well aware of open educational resources. E PG Path Shala is the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The advantages are that it entices students to learn, has a high level of clarity in delivering material, is easily accessible, and supports student learning skills (Salehudin, 2020). Learning videos are a product of an increasingly modern and growing educational paradigm (Midha & Kumar, 2022).…”
Section: Figure 2 the Results Of The Small-group Trialmentioning
confidence: 99%
“…The advantages are that it entices students to learn, has a high level of clarity in delivering material, is easily accessible, and supports student learning skills (Salehudin, 2020). Learning videos are a product of an increasingly modern and growing educational paradigm (Midha & Kumar, 2022).…”
Section: Figure 2 the Results Of The Small-group Trialmentioning
confidence: 99%
“…A comprehensive analysis of the relationship between open access and OER revealed that these initiatives share the same connotation because they address issues of information in the public domain ( Gowran et al., 2021 ; Huang et al., 2020 ). The existing distinct literature affirms that the development of open access was more concerned about research ( Appavoo and Pagotto, 2014 ; Hermans, 2017 ; Papin-Ramcharan, 2006 ), while OER concerned teaching and learning ( Pawlowski, 2012 ; Midha & Kumar, 2022 ). Both OER and open access succeeded through utilisation of ICT for tuition and research provision in higher education institutions ( Huang et al., 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The essence of OER is identified as a great enabler of affording open and free access to education ( Admiraal, 2022 ). OER affords wider opportunities for educational access globally and brings technological advancements in educational spaces ( Midha & Kumar, 2022 ). OER initiatives have been made possible by advancements in various technologies, such as internet bandwidth quality, accessible computers, and mobile computers ( Fulgencio and Asino, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study further revealed that Academics in the sciences showed more promise of adopting OER as authors and readers of scholarly resources than their counterparts in the humanities, even though the study found minimal utilization among the academic staff. A study conducted by Midha and Kumar (2022) also established that the academic community of central universities in North India was aware of OERs and that the majority used OERs when they were required, with YouTube being the most frequently used OER. Furthermore, a study by Ogunleye and Okhakhu (2022) on "assessing academic staff awareness and use of open access resources in polytechnics in Lagos State" discovered that while academic staff members were aware of OERs, they encountered several obstacles when trying to use them, such as poor-quality articles, a lack of search abilities, and delayed network connectivity.…”
Section: Awareness Of Oermentioning
confidence: 99%